Product Development Strategies Impact The Purchasing Interest Of Coffee Kali Drinkers - Nazla Kaylasalma; Abriandi Abriandi; Virgo Simamora (ITB AAS Indonesia Surakarta, 2025)
The purpose of this study is to explain the influence of product development strategy on purchasing interest Kali Coffee. This research have 100 respondents who qualify to be a respondent in this research. The data collection technique in this research was carried out by distributing questionnaires via Google form. The researcher used PLS-SEM as a data analysis with Smartpls 3.0 software support. The result of this research indicate that product development strategy have an effect on purchasing interest Kali coffee.